Cost comparison of axillary sentinel lymph node detection and axillary lymphadenectomy in early breast cancer. A national study based on a prospective multi-institutional series of 985 patients ‘on behalf of the Group of Surgeons from the French Unicancer Federation’ - Classe, J.M.; Baffert, S.; Sigal-Zafrani, B.; Fall, M.; Rousseau, C.; Alran, S.; Rouanet, P.; Belichard, C.; Mignotte, H.; Ferron, G.; Marchal, F.; Giard, S.; et al. (Annals of oncology, 2012)
Our objective was to assess the global cost of the sentinel lymph node detection [axillary sentinel lymph node detection (ASLND)] compared with standard axillary lymphadenectomy [axillary lymph node dissection (ALND)] for early breast cancer patients. We conducted a prospective, multi-institutional, observational, cost comparative analysis. Cost calculations were realized with the micro-costing method from the diagnosis until 1 month after the last surgery. Eight hundred and thirty nine patients were included in the ASLND group and 146 in the ALND group. The cost generated for a patient with an ASLND, with one preoperative scintigraphy, a combined method for sentinel node detection, an intraoperative pathological analysis without lymphadenectomy, was lower than the cost generated for a patient with lymphadenectomy [€2947 (σ = 580) versus €3331 (σ = 902); P = 0.0001]. ASLND, involving expensive techniques, was finally less expensive than ALND. The length of hospital stay was the cost driver of these procedures. The current observational study points the heterogeneous practices for this validated and largely diffused technique. Several technical choices have an impact on the cost of ASLND, as intraoperative analysis allowing to reduce rehospitalization rate for secondary lymphadenectomy or preoperative scintigraphy, suggesting possible savings on hospital resources.